2015
DOI: 10.1007/s11947-015-1515-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Short-Term Postharvest Ozone Treatments in Nitrogen or Air Atmosphere on the Metabolic Response of White Wine Grapes

Abstract: This PhD thesis aimed to clarify the effects due to different ozone postharvest treatments on quality traits and accumulation of phenolic healthy compounds in white wine grapes, belonging to Grechetto cv. The thesis also aimed to investigate whether and how the ozone treatments could affect the flavor profile of the grapes. Finally, it aimed to apply one of the most used chemometric tools, the principal component analysis (PCA), to gain insights into variations in the nutritional profiles between different pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 68 publications
5
66
0
4
Order By: Relevance
“…Total polyphenol content (TPC) and flavan-3-ol content (FLC) of extracts were determined according to Carbone and Mencarelli (2015). Data were expressed as mg of gallic acid equivalents (GAE) and mg catechin equivalents (CAE) per g on DM for TPC and FLC, respectively.…”
Section: Extraction and Analysis Of Phytochemical Content And Antiradmentioning
confidence: 99%
See 1 more Smart Citation
“…Total polyphenol content (TPC) and flavan-3-ol content (FLC) of extracts were determined according to Carbone and Mencarelli (2015). Data were expressed as mg of gallic acid equivalents (GAE) and mg catechin equivalents (CAE) per g on DM for TPC and FLC, respectively.…”
Section: Extraction and Analysis Of Phytochemical Content And Antiradmentioning
confidence: 99%
“…Both DPPHÁ and ABTSÁ ? quenching capacities were estimated spectrophotometrically according to Carbone and Mencarelli (2015), and expressed in terms of EC 50 .…”
Section: Extraction and Analysis Of Phytochemical Content And Antiradmentioning
confidence: 99%
“…Ozone generally induces a variety of physiological changes in fruits and vegetables (Dickson, Kays, Law, & Eiteman, 1992;Forney, Song, Fan, Hildebrand, & Jordan, 2003;García-Martín et al, 2018;Han et al, 2014;Skog & Chu, 2001). In this regard, O 3 can be considered a postharvest elicitor that promotes the accumulation of a variety of beneficial phytochemicals in crops (Carbone & Mencarelli, 2015). Studies have reported that strawberries treated with ozone contain three times the level of vitamin C than untreated, control fruit after 3 days of cold storage (Pérez, Sanz, Ríos, Olías, & Olías, 1999) and that apples treated with ozone have lower weight loss and spoilage in storage (Skog & Chu, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Like flavonoids, phenolic acids are secondary metabolites crucial for plant growth and reproduction and whose production can be affected by the environment or post‐harvest process . Derivates from phenolic acids such as, caffeoylthreonate (peak number 1) and caffeic acid hexoside (peak number 4) are disturbed in strawberry fruit after the storage under 20% CO 2 + 5% O 2 atmosphere at 0°C for 2 days.…”
Section: Resultsmentioning
confidence: 77%
“…Like flavonoids, phenolic acids are secondary metabolites crucial for plant growth and reproduction 30 and whose production can be affected by the environment or post-harvest process. 39,40 Derivates from phenolic acids such as, caffeoylthreonate (peak number 1) and 31 In addition, 4-(2-hydroxyethyl)phenol-hexoside (peak The use of DI-MS in positive ion mode do not allow the distinction between cyanidin-3-glucoside or cyanidin-3-galactoside, in this case, therefore it is necessary to use a complementary chromatographic technique for better identification. During the maturation of the fruit, the content of the anthocyanins increases 42,43 though, the amount of these pigments varies depending on the variety, crop and can be affected after post-harvest treatments.…”
Section: Di-esi-qqq-tof-ms Analysismentioning
confidence: 99%